2017
DOI: 10.1371/journal.pone.0169671
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Gene Expression Profiles between Glucocorticoid Responder and Non-Responder Bovine Trabecular Meshwork Cells Using RNA Sequencing

Abstract: The most common ocular side effect of glucocorticoid (GC) therapy is GC-induced ocular hypertension (OHT) and GC-induced glaucoma (GIG). GC-induced OHT occurs in about 40% of the general population, while the other 60% are resistant. This study aims to determine the genes and pathways involved in differential GC responsiveness in the trabecular meshwork (TM). Using paired bovine eyes, one eye was perfusion-cultured with 100nM dexamethasone (DEX), while the fellow eye was used to establish a bovine TM (BTM) cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(63 citation statements)
references
References 67 publications
8
46
0
Order By: Relevance
“…Bermudez et al 14 kindly provided the complete statistical results of their RNA-sequencing experiment: the averaged Fragments Per Kilobase Million (FPKM) for each tested gene after exposure to dexamethasone and a control medium in both responders and nonresponders.…”
Section: Preprocessing Of the Bovine Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Bermudez et al 14 kindly provided the complete statistical results of their RNA-sequencing experiment: the averaged Fragments Per Kilobase Million (FPKM) for each tested gene after exposure to dexamethasone and a control medium in both responders and nonresponders.…”
Section: Preprocessing Of the Bovine Datamentioning
confidence: 99%
“…After the systematic search, the datasets of five different human microarray studies were selected for further analyses: GSE6298 (Fan et al 6 ), GSE16643 (Nehmé et al 10 ), GSE37474 (Kwon et al, 8 concept article received after contacting the authors), GSE65240 (Matsuda et al 9 ), and GSE124114 (Faralli et al 31 ) In addition, the statistical results of the bovine RNA-sequencing experiment by Bermudez et al 14 were used in the analysis.…”
Section: Included Datasetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical trials have shown that more than 90% of POAG patients are steroid responders. It has been suggested that steroid responders are at greater risk for development of POAG [12][13][14][15] .…”
Section: Steroid Responders and Steroid-induced Iop Elevationmentioning
confidence: 99%
“…Many of GC-induced changes in TM of human eyes can be mimicked in cultured TM cells, indicating a direct action of GCs on TM [48]. Transcriptomic and proteomic analysis of DEX-treated cultured human and bovine TM cells revealed alteration in hundreds of genes and proteins involved in cell metabolism, signal transduction, cell structure/motility, intracellular traffic, and immunity [49–51]. Moreover, DEX induced the upregulation of noncanonical Wnt ligand Wnt5a , which in turn induced cross-linked actin network (CLAN) formation in cultured TM cells through RhoA/ Rho-associated protein kinases (ROCK) [5254].…”
Section: Introductionmentioning
confidence: 99%